Semantic Structure of Concept «Macht» in German Cultural Studies: Psycholinguistic Aspect - Olesia Skliarenko (Психолінгвістика, 2018)
The article reveals some peculiarities of semantic structure of concept «MACHT» functioning in German cultural studies. The analyses of lexicographic objectification of the name of the concept «MACHT» has been done, which points to some peculiarities chain in conceptual way of thinking of the studied mental unit in German cultural studies. The given facts let us suggest, that the model of composites forming with derivative element– macht are productive for German lingual environment and point to their semantic actuality and high recurrence of the given mental unit in conceptual world picture. Lexical and semantic connections of concept verbalizator «MACHT» of the lexem «Macht», which were analyzed in the proposed article point to the polisemantic structure of the actual word. Collocational analyses has shown, that semantic peculiarities of function of concept «MACHT» are actually in the word, which is its name - «Macht» and are mostly used in connection with attributes and predicates. The collocation quantity with the lexemes proves that there are some actual language collocations, where the analyzed lexeme is used in communicative area. It was established, that among the main verbalizators of the concept «MACHT» phraseological units are rather wide spread. These phraseological units objectivize all maim concept slots, such as «Action», «Object of Power» and «Subject of Power». Besides we have come to conclusion that research of individual word meaning taking into consideration some association words gives the possibility not only to establish the fact of word meaning change but also to analyze the change of individual world picture of German speaking society and give some predictions about negative changes on German political stage.